Significance and possibilities of caries risk assessment in children - Stojković Branislava; Igić Marija; Tričković-Janjić Olivera; Stojanović Simona; Topalović Marija (Medicinski fakultet i Klinika za stomatologiju, Niš, 2018)
Introduction: as a process of determining the likelihood of developing a new carious lesion in a given person within a specific period of time and/or the likelihood of changes occurring in severity and/or activity within existing lesions. In the last decades, the emphasis has been put on personalized preventive approach that provides individual estimation of caries risk. The aim: The aim of this study was to emphasize the significance and possibilities of caries risk assessment in children. Conclusion: Further research in this field should be aimed at distinguishing unique caries risk factor or the combination of factors that would show high caries predictive importance, and to allow very early identification of an individual/population group at risk before a clinical manifestation of the disease.